Stitching love and loss : a Gee's Bend quilt - Collins, Lisa Gail (Seattle : University of Washington Press, 2023)
"In 2000, nearly six decades after her father's death, Arlonzia Pettway remembered vividly how, in 1942, her mother, newly suffering the loss of her husband and the father of their children, pieced together a quilt out of his old, worn work clothes. Approaching eighty at the time and a seasoned quilt maker herself, Arlonzia Pettway readily recalled this quilt made by her grieving mother--and involving her own bereaved assistance. In Love Lies Here, Collins examines the small African American farming community of Gee's Bend, Alabama, through a quilt made by Arlonzia's mother, Missouri Pettway, to argue that this woman's quilt and her daughter's remembrance of it shine light on essential questions of living, dying, and grieving"--
Introduction: Missouri Pettway's Quilt Made in Mourning -- Woven within the Land -- Carrying History and Memory -- Seeking Sanctuary -- Lined with Labor -- Shared Care and Prayer -- Conclusion: Sacred Utility -- Coda: Pulled to This Place.
Includes bibliographical references and index.
JSTOR
Keywords: Pettway, Arlonzia, -- 1923- -- Family; Boykin (Wilcox County, Ala.) -- Social conditions; African Americans -- Alabama -- Boykin (Wilcox County) -- Social conditions; African American quiltmakers -- Alabama -- Boykin (Wilcox County); Quilting -- Psychological aspects; Quilting -- Alabama -- History; Commemorative quilts -- Alabama; Boykin (Wilcox County, Ala.) -- Social life and customs; Mourning customs -- Alabama; Deuil -- Coutumes -- Alabama; SOCIAL SCIENCE / Ethnic Studies / American / African American & Black Studies; African American quiltmakers; African Americans -- Social conditions; Commemorative quilts; Families; Manners and customs; Mourning customs; Quilting; Social conditions; Alabama; Alabama -- Boykin (Wilcox County); Electronic books; History